2003
DOI: 10.1002/uog.26
|View full text |Cite
|
Sign up to set email alerts
|

Inutero development of the fetal colon and rectum: sonographic evaluation

Abstract: Objective To construct a normal range for the internal diameter of the fetal descending colon and rectum during gestation. Subjects and Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
79
5
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 9 publications
18
79
5
1
Order By: Relevance
“…In contrast with our study, Parulekar 13 reported a visualization rate of fetal colon of only 44% between 18 and 25 weeks. Our higher visualization rate, similar to that in the study by Zalel et al, 10 likely results from improved resolution of the US equipment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast with our study, Parulekar 13 reported a visualization rate of fetal colon of only 44% between 18 and 25 weeks. Our higher visualization rate, similar to that in the study by Zalel et al, 10 likely results from improved resolution of the US equipment.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the wall of fetal anal canal appears as an area of hypoechogenicity, and the lumen appears as a central echogenic line. Zalel et al 10 measured the fetal descending colon and rectum and reported a nonlinear relationship with menstrual age (R 2 of 0.848 and 0.831, respectively) with a maximum colon diameter of 18 mm. Bourdelat et al 15 also studied the US appearance of the fetal anal sphincter.…”
Section: Discussionmentioning
confidence: 99%
“…These results were similar to the findings of Zalel et al and Nyberg et al who found that colon diameter demonstrated a linear relationship with menstrual age, reaching a maximum of 18 mm at term. 12,13 In this study, we found that for fetuses with colon diameter equal to or greater than 12mm, 58.7% were 37 weeks or older, with a sensitivity of 81.8% and specificity of 71.6%. For fetuses with colon diameter equal to or greater than 14 mm, 64.7% were 37 weeks or older with a sensitivity of 33.3% and specificity of 91.0%.…”
Section: Discussionmentioning
confidence: 50%
“…10 Although many studies have been done among western population to determine the relationship between various features of the intestinal development and the gestational age, there is paucity of data from Indian population. 3,5,[11][12][13] In this study, we have studied the relationship of maximum diameter of the fetal descending colon with the gestational age between 32 to 40 weeks of gestation and tried to verify whether fetal colon diameter can be used for estimating the gestational age of fetuses among Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…İnce ve kalın barsakların genişlikleri gebelik haftası ile birlikte artış gös-termekte olup gebelik haftasına göre nomogramlar bulunmaktadır [4,5]. Üçüncü trimesterde ince barsak çapları 7 mm'yi, uzunlukları 15 mm'yi; inen kolon çapı 18 mm'yi, rektum çapı…”
Section: Gastrointestinal Sistemin Normal Ultrason Görünümüunclassified